Variations of preseason conditioning on volleyball performance - Nesser, T. W.; Demchak, T. J. (Journal of Exercise Physiology online, 2007)
Variations of preseason conditioning on volleyball performance. JEP online 2007:10(5):35-42. Over two competitive seasons (04--05 and 05-06), NCAA Division I female volleyball players (ht 177.9 ± 5.6 cm, wt 70.2 ± 3.8 kg and ht 175.5 ± 8.0 cm, wt 67.4 ± 7.5 kg, respectively) completed two weeks of preseason multiple daily practices. The 04-05 preseason consisted of 24 practice sessions, 12 resistance-training sessions, and 2 rest days within a 14-day period. The 05-06 preseason consisted of 17 practice sessions, 10 resistance-training sessions, and 1 rest day within a 14-day period. Players completed three performance variables prior to the start of preseason conditioning (PPS), following preseason conditioning (PTPS), and post regular season (PTS). Performance variables include a spike vertical jump (SVJ), a block vertical jump (BVJ), and a T-run agility test (TRUN). t-tests were used for data analysis. Results (04-05): SVJ decreased between PPS (52.1 ± 2.9 cm) and PTPS conditioning (48.8 ± 3.4 cm, p = 0.000), but returned to PPS levels by PTS (54.5 ± 3.9 cm, p = 0.03). BVJ decreased between PPS (47.5 ± 3.1 cm) and PTPS (39.8 ± 3.7 cm, p = 0.000) and remained low (PTS 44.3 ± 4.7 cm, p = 0.016). TRUN increased in time between PPS (10.12 ± 0.5 sec) and PTPS (10.33 ± 0.7 sec, p = 0.027). TRUN returned to PPS levels by PTS (10.10 ± 0.5 sec, p = 0.001). Results ('05-'06): SVJ and BVJ experienced no change at PTPS (52.0 ± 2.9 cm vs. 52.9 ± 3.9 cm, p = 0.48 and 40.9 ± 3.3 cm vs. 41.9 ± 3.5 cm, p = 0.15) or PTS (54.6 ± 3.5 cm, p = 0.08 and 42.0 ± 3.5 cm, p = 0.87). TRUN improved at PTPS (10.01 ± 0.6 sec vs. 9.69 ± 0.6 sec, p = 0.006) and continued to improve by PTS (9.17 ± 0.8 sec, p = 0.003). Conclusions: The results of this study suggest multiple practices in the preseason can be beneficial pending sufficient rest and recovery. ABSTRACT FROM AUTHOR